An economic assessment of adoption of hybrid rice: Micro-level evidence from southern China - Yan, Zedong; Chen, Fengbo; Mishra, Ashok K.; Sha, Wenbiao (Frontiers in Sustainable Food Systems, 2022)
The hybrid rice technology could be considered a boon for food security for many in South and Southeast Asia to increase rice productivity. In China, the birthplace of hybrid rice (HR), the diffusion of hybrid rice started in 1976. About 28% rice-growing area in China is planted with hybrid rice. However, the proportion of HR area in China has been declining in recent years, and farmers in surrounding countries are reluctant to adopt it because of high seed costs, farm management practices, and quality issues. Most previous research on the evaluation of hybrid rice variety on yield does not control input level. This study uses the endogenous switching regression method to analyze the impacts of HR adoption on rice yield and net rice income. The study uses plot- and household-level data from four southern provinces of China. Findings show a significant effect of HR adoption on rice yields. On the same HR plots, compared to CR adopters, rice yield increases by 4.86% for HR adopters. Rice yield would increase by 4.72% if the HR variety was adopted on the same conventional rice (CR) plots. Additionally, findings show a significant effect of HR adoption on net rice incomes. On the same HR plots, compared to CR adopters, net rice income decreases by 43.61% for HR adopters. Similarly, net rice income would reduce by 10.95% if the HR variety was adopted on the same CR plots. Thus, adopting HR increases rice productivity, but Chinese farming households that adopted CR would not benefit from adopting HR. Policymakers can formulate a systematic and comprehensive rice breeding plan to guide the simultaneous development of rice variety yield and quality improvement. Additionally, policymakers, in conjunction with private companies, could enact policies to reduce the cost of hybrid rice seed or improve the production efficiency of HR. For example, they could incentivize the development of HR varieties suitable for direct seeding and seed-saving sowing methods (rice trans-planter).